2013
DOI: 10.1158/1541-7786.mcr-13-0172
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mTOR Pathway Sensitizes Acute Myeloid Leukemia Cells to Aurora Inhibitors by Suppression of Glycolytic Metabolism

Abstract: Aurora kinases are overexpressed in large numbers of tumors and considered as potential therapeutic targets. In this study, we found that the Aurora kinases inhibitors MK-0457 (MK) and ZM447439 (ZM) induced polyploidization in acute myeloid leukemia (AML) cell lines. The level of glycolytic metabolism was significantly increased in the polyploidy cells, which were sensitive to glycolysis inhibitor 2-deoxy-D-glucose (2DG), suggesting that polyploidy cells might be eliminated by metabolism deprivation. Indeed, i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 58 publications
8
52
0
1
Order By: Relevance
“…In addition, AKI603 treatment initially resulted in G2/M cell cycle arrest and significant degree of aneuploidy (Fig. 2), a typical phenotype of Aurora suppression (24). These data were consistent with our finding in AML and solid tumor cells that inhibition of Aurora induced cell cycle arrest, promoted polyploidy formation and inhibited cell proliferation (24-26).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, AKI603 treatment initially resulted in G2/M cell cycle arrest and significant degree of aneuploidy (Fig. 2), a typical phenotype of Aurora suppression (24). These data were consistent with our finding in AML and solid tumor cells that inhibition of Aurora induced cell cycle arrest, promoted polyploidy formation and inhibited cell proliferation (24-26).…”
Section: Discussionsupporting
confidence: 89%
“…Disruption of Aurora kinase activity induces abnormal spindle pole organization, centrosome separation and chromosome congression (23). Ultimately, cells treated with Aurora kinase inhibitor undergo cell growth inhibition through the development of deleterious aneuploidy (24,25). In this report, we found that AKI603 inhibited Aur-A kinase and presented anti-leukemia effects in KBM5 cells, as well as KBM5-T315I cells, suggesting a possible novel and potent target in treating imatinib-resistant CML.…”
Section: Discussionmentioning
confidence: 61%
“…Inhibition of Aurora-A kinases could inhibit proliferation, viability, migration, and invasion of gastric cancer cells [6]. Recent studies showed that kinase inhibition of Aurora-A triggered autophagy in breast cancer and leukemia cells [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…These polyploid cells showed increased consumption of glucose and increased production of lactase. Cell viability decreased with increasing concentration of 2-DG [23]. Expression of mutant Cbl (Casitas B-lineage lymphoma) proto-oncogene (CBL) in FLT3-expressing Ba/F3 cells increased ROS production and enhanced glucose consumption.…”
Section: Hexokinase Inhibitorsmentioning
confidence: 99%